Radiology Comprehensive Review of Radiology in Emergency Medicine: Rapid Diagnostics and Clinical Outcomes - ALRASHDI, MOHAMMED MAQBUL MUADDI; SHEMMRY, SALEM NAZAL FALAj; ALJARWAN, ASMA FAHAD SAUD; ALHARBI, ABDUALRAHMAN SHUTIT MOFADHI; ALSHAMMARI, SALMAN GHAFIL S; ALRASHIDI, SHAKER AYIDH THEAB; ALSHAMMARI, YOUSEF DHAIFALLAH SAYER; MOHAMMAD A, ALMALAQ,SALEH; ALANAZI, SULAIMAN MOHAMMED S; ALSHAMMARI, YOUSEF SALEM SADI (Journal of Ecohumanism, 2024)
Emergency medicine depends on the speed by which a particular diagnosis can be made to guide subsequent patient management. Radiology is central to this process, especially where high-stress conditions demand efficiency. Whether CTs and MRIs, ultrasounds, or X-rays, advanced imaging makes quick and effective diagnoses affecting patient outcomes. This review then focuses on including radiology in emergency medicine, the functions of different types of images, the advantages of early diagnosis, and issues related to personnel handling urgent situations.